Aerobic exercise as a non-pharmacological intervention to reduce weight gain in 3-month injectable contraceptive users - Zulhijriani Zulhijriani; Nur Cahyani Ari Lestari; Salwa Annisaa; Luluk Yuliati (Institute of Computer Science (IOCS), 2026)
Weight gain is identified as one of the most prevalent side effects among users of 3-month injectable contraceptives (Depot Medroxyprogesterone Acetate/DMPA), which significantly impacts user compliance and long-term health. This study aims to analyze the effect of a structured aerobic exercise intervention on weight reduction among DMPA users. This research employed a quantitative pre-experimental design with a pretest-posttest approach. The study was conducted in Tondomulyo Village, Pati District, Central Java, involving 50 women of reproductive age (15–49 years) who were current users of 3-month injectable contraceptives, selected through purposive sampling. Body weight was measured before and after the intervention using calibrated digital scales. Data were analyzed using a paired sample t-test via SPSS with a significance level of p < 0.05. The study found a statistically significant decrease in body weight following the aerobic exercise intervention (p=0.000). The mean body weight decreased from 61.92 kg at pre-intervention to 60.86 kg post-intervention, resulting in a mean difference of 1.06 kg. Most participants engaged in light-intensity exercise (58%), though regular exercise was associated with more optimal metabolic outcomes. Aerobic exercise is an effective non-pharmacological intervention for managing weight gain among DMPA users. Incorporating structured physical activity into reproductive health programs can serve as a holistic approach to mitigate contraceptive side effects and improve user continuation rates.